A psychoanalytic exploration of the contemporary search for pleasure the turning of the screw - Tsolas, Vaia; Anzieu-Premmereur, Christine (Routledge, Taylor & Francis Group, 2024)
"This interdisciplinary collection of essays explores the malaise of the contemporary individual by returning the economic point of view of Freudian thinking, the concept of satisfaction, libido and pleasure-unpleasure principle to their rightful place as the motivating forces of human existence. For Freud, pleasure stands apart from other human experiences, side by side with unpleasure, always a bonus in the search for satisfaction of the pleasure principle and beyond. Along with libido, emotional fulfilment, and the capacities for sublimation and play, pleasure has not been given enough attention in the psychoanalytic literature. The editors of this book address this lack and highlight the importance of examining today's social and individual malaise through these specific lenses of inquiry. It is particularly timely and important today to address this lack, and thereby examine the impact of the social phenomena of the pandemic, the crises of ideals and virtuality on the subject who feels in a state of constant emergency, overwhelmed, addicted and delibidinalized. With contributions from across psychoanalysis, this book is essential reading for psychoanalysts in training and in practice who want to understand how the modern world has shaped our understanding of pleasure."
Keywords: Lust; Psychoanalyse; Befriedigung; Satisfaction; Pleasure; Psychoanalysis; Aufsatzsammlung